Metode Simple Multi Attribute rating Technique (SMART) Dalam Menentukan Penerima Dana Bantuan Yayasan AMIK Tunas Bangsa - Andani, Sundari Retno (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
Foundation grants are funds that comes from foundation and given for student achievement and poor, which aims to prevent collage drop outs for students. The criteria used in determining the foundation grant recipients are GPA, parent’s income and the number of dependents. The method applied in determining the foundation grant recipients is SMART (Simple Multi Attribute rating Technique) method. Because this method able to solve the multicriteria decision making problems, base on theory that each criteria has a weight that describes how important these criteria with other criteria. The results of this research are recommendations from recipients of foundation grant.